Diabetic foot ulcer management in a multidisciplinary foot centre: one-year healing, amputation and mortality rate. (2nd August 2020) - Ha Van, Georges; Amouyal, Chloe; Bourron, Olivier; Aubert, Carole; Carlier, Aurelie; Mosbah, Helene; Fourniols, Eric; Cluzel, Philippe; Couture, Thibault; Hartemann, Agnes
Abstract : Objective: To describe the rates of healing, major amputation and mortality after 12 months in patients with a new diabetic foot ulcer (DFU) and their care in a French diabetic foot service (DFS). Method: A prospective single-centre study including patients from March 2009 to December 2010. The length of time to healing, minor amputation, major amputation and mortality rate after inclusion were analysed using the Kaplan–Meier method. Results: Some 347 patients were included (3% lost to follow-up), with a median follow-up (IQR) of 19 (12–24) months. The mean (SD) age was 65±12 years, 68% were male, and the median duration of the ulcer was 49 (19–120) days. Complications of the DFU were ischaemia (70%), infection (55%) and osteomyelitis (47%). Of the patients, 50% were inpatients in the DFS at inclusion (median duration of hospitalisation 26 (15–41) days). The rate of healing at one year was 67% (95% confidence interval (CI): 61–72); of major amputation 10% (95% CI: 7–17); of minor amputation 19% (95% CI: 14–25), and the death rate was 9% (95% CI: 7–13). Using an adjusted hazard ratio, the predictive factors of healing were perfusion and the area of the wound. The risk factors for a major amputation were active smoking and osteomyelitis. The risk factors for mortality were perfusion and age. Conclusion: This study confirms the need to treat DFUs rapidly, in a multidisciplinary DFS.